Pengembangan Budaya Literasi melalui Metode Fresh-Reading untuk Meningkatkan Minat Membaca Siswa di SD Negeri 150 Palembang - Lestari, Widiya; Meidika, Meidika; Afandi, Muhamad (Postgraduate Study Programme, Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2025)
This article discusses the use of the Fresh-Reading method for the development of a culture of liberation in fostering students' interest in reading at SD Negeri 150 palembang. The Fresh-Reading method is a learning approach that emphasizes students' active involvement in reading in a fun and relevant way to their lives. The purpose of this study was to see the impact of implementing the Fresh-Reading method in creating a positive reading culture and increasing students' interest in reading. The results of implementing this method show an increase in students' enthusiasm in reading as well as success in introducing literacy concepts that focus on freedom of thought and exploration of ideas. In addition, the implementation of this method also helps students to better appreciate reading materials and build better literacy skills. Despite challenges in the initial transition, this approach has proven effective in encouraging students to be more active in reading activities. Overall, the Fresh-Reading method at SD Negeri 150 palembang contributes significantly to developing a culture of liberation and increasing students' interest in reading.